2002
DOI: 10.1021/jp0143903
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Hydrophobic Interaction of Dissymmetric Gemini Surfactants in Aqueous Solutions

Abstract: We have used microcalorimetry to measure the critical micelle concentrations (CMC) and enthalpies of micellization (ΔH mic) of the series of dissymmetric cationic gemini surfactants, [C m H2 m +1(CH3)2N(CH2)6N(CH3)2C n H2 n +1]Br2, designated as C m C6C n Br2, with constant n + m = 24 and n = 6, 8, 10, 11, 12. There is a small decrease in CMC as the ratio m/n increases but this decrease is not much larger than the error. On the other hand there is a very large decrease in the enthalpy of micellization with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 38 publications
9
81
0
1
Order By: Relevance
“…Temperature on π-A Isotherms of Asymmetrical Gemini As described in the previous section, C 13 -C 15 was found to form a clear solid phase upon compression at 12.3 . To discuss the effect of the temperature on π-A isotherms of asymmetric geminis, π-A measurements were carried out at various temperatures T sub 7.3 -42.…”
Section: Effect Ofsupporting
confidence: 56%
See 4 more Smart Citations
“…Temperature on π-A Isotherms of Asymmetrical Gemini As described in the previous section, C 13 -C 15 was found to form a clear solid phase upon compression at 12.3 . To discuss the effect of the temperature on π-A isotherms of asymmetric geminis, π-A measurements were carried out at various temperatures T sub 7.3 -42.…”
Section: Effect Ofsupporting
confidence: 56%
“…As an example of the view point of asymmetry in hydrophobic chains, Bai et al measured the dilution enthalpies of C m C 6 C n Br 2 with m n 24 and -CH 2 6 -spacer, and concluded that a large interaction energy is associated with the addition of a CH 2 to the long alkyl chain than that to the short alkyl chain 13 . According to Zana, however, the distance between two headgroups of C m C 6 C n Br 2 would be comparable to that between two similar monomer units.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations